Efficient nursery production and multiple-shoot clumps formation from shoot tiller-derived shoot apices of dwarf napiergrass (Pennisetum purpureum Schumach.) - Nafiatul Umami, N. Umami (Journal of Warm Regional Society of Animal Science, Japan, 2012)
The objective of this study was to improve an in vitro tissue culture system for the dwarf napiergrass l.Pennisetum purpureum Schumach.). Additionally, it was needed special treatments for acclimatization, and carried the risks of somaclonal variation and physiological aberations. Shoot apices as initial explants were isolated aseptically from shoottillers, and cultured on in vitro MS (Murashige and Skoog, 1962) medium containing 3.002 sucrose and 0.3o/o phytagel. The most effective phltohormone treatment for multiple-shoot clumps (MSCs) induction was 0.1 mg L-l 2,4-D plus 2.0 mg L-1 BAP. The addition of 50 p M CuSO+ could increase the percentage of MSCs proliferation. Plant regeneration frequency was achieved up to 84%o by culturing the MSCs on solid MS medium containing 0.1 mg L-1 NAA and2.0 mg L-l BAP. A11 regenerants were successfully grown up in the soil. Compared to control plants, in vitro regefierated plants did not reveal any significant difference (P > 0.05) on morphological characteristics and DNA content. The results of this study suggest that improved protocols for in vitro propagation would provide high quality nursery plant production of dwarf napiergrass in grassland field.